Conocimientos y prácticas de autocuidado sobre enfermedades crónico-degenerativas en docentes del colegio “Nuestra Señora del Rosario” – Catamayo - Luzuriaga Soto, Stefania Anabel (2022)
Chronic-degenerative diseases are slowe-moving pathologies without immediate cure, which arise from modifiable risk factors such as poor diet, sedentary lifestyle, tobacco or alcohol consumption, or by non-modifiable factors such as hereditary, age, sex and ethnicity; in the manifestation of symptoms apart from pharmacological treatment, habits harmful to health must be modified. The general objective of this research work is to determine the knowledge and practices of self-care on chronic degenerative diseases of teaching staff, for the implementation of strategic proposals for self-care. It was a quantitative-descriptive cross-sectional study, in which 83 teachers participated, to whom a survey was applied, obtaining as a result: that 38,6% of teachers are in a range of 31 to 40 years of age; a 74,7% belong to the female sex; and 55,4% are married, 71% have a good knowledge regarding the concept, symptoms and complications of the most common chronic degenerative diseases, such as mellitus diabetes, hypertension, breast cancer, obesity and overweight; in relation to sell-care a 71,1% practice a sport or exercise; 100% have a varied diet; 97,6% do not consume tobacco; however, 48.2% eat junk food; 35% and 37.3% consume carbonated drinks and alcoholic beverages respectively. In conclusion, teachers have a very good knowledge and carry out self-care practices on chronic-degenerative diseases; finally, the educational proposal was delivered against the most frequent degenerative chronic diseases and sel-care practices, which will contribute to the reduction of complications in the study group